Mapping of the Structural Genes of the Three Aspartokinases and of the Two Homoserine Dehydrogenases of Escherichia coli K-12 - Thèze, J. (1974)
Mutants requiring threonine plus methionine (or homoserine), or threonine plus methionine plus diaminopimelate (or homoserine plus diaminopimelate) have been isolated from strains possessing only one of the three isofunctional aspartokinases. They have been classified in several groups according to their enzymatic defects. Their mapping is described. Several regions of the chromosome are concerned: thrA (aspartokinase I-homoserine dehydrogenase I) is mapped in the same region as thrB and thrC (0 min). lysC (aspartokinase III) is mapped at 80 min, far from the other genes coding for diaminopimelate synthesis. metLM (aspartokinase II-homoserine dehydrogenase II) lies at 78 min closely linked to metB, metJ, and metF.